Students’ Perception of Discovery Learning in Microteaching Class - Yosannia Arnaz; Aryuliva Adnan (Universitas Negeri Padang, 2021)
Discovery Learning as one of the methods proposed by the 2013 curiculum are suggested learning methods for teachers to increase students' activeness and critical thinking. However, discovery learning also has its downside such as it can be a very time-consuming method. This advantages and disadvantages resulted in microteaching students having different perceptions on the discovery learning. The purpose of this study is to describe students’ perceptions of discovery learning in microteaching class at English Department, Universitas Negeri Padang. This research used descriptive quantitative research. The sample for this research was 56 microteaching students of English Department in Universitas Negeri Padang. The data collection technique used in this research was a questionnaire with 6 indicators through google form application. Therefore, the results of this study showed that the majority of microteaching students in English Department had a positive or good perception of the implementation of discovery learning. The students agree that the use of discovery learning motivates students to be more active in class, improves students’ critical thinking, interpretation, communication, collaboration skills. However, the microteaching students still encounter obstacles to encourage the students to answer the question and be active in the class.